Does the graft-tunnel friction influence knee joint kinematics and biomechanics after anterior cruciate ligament reconstruction? A finite element study. Issue 3 (17th February 2018) - Wan, Chao; Hao, Zhixiu
Abstract: Graft tissues within bone tunnels remain mobile for a long time after anterior cruciate ligament (ACL) reconstruction. However, whether the graft-tunnel friction affects the finite element (FE) simulation of the ACL reconstruction is still unclear. Four friction coefficients (from 0 to 0.3) were simulated in the ACL-reconstructed joint model as well as two loading levels of anterior tibial drawer. The graft-tunnel friction did not affect joint kinematics and the maximal principal strain of the graft. By contrast, both the relative graft-tunnel motion and equivalent strain for the bone tunnels were altered, which corresponded to different processes of graft-tunnel integration and bone remodeling, respectively. It implies that the graft-tunnel friction should be defined properly for studying the graft-tunnel integration or bone remodeling after ACL reconstruction using numerical simulation.